The quality awareness of the construction workers in Malaysian construction industry [electronic resource] - Mohd. Fazli Mohamad, 1982-, author (2012)
Project Paper (Sarjana Muda Kejuruteraan (Awam - Pengurusan Pembinaan)) - Universiti Teknologi Malaysia, 2012